Reseña de Hogan, P. C. (2003). The Mind and its Stories. Narrative Universal and Human Emotion. - Eizaga Rebollar, Bárbara (Pragmalingüística, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Se trata de una reseña de Hogan, P. C. (2003). The Mind and its Stories. Narrative Universal and Human Emotion.